Malaria in Hadhramout, a Southeast Province of Yemen: Prevalence, Risk Factors, Knowledge, Attitude and Practices (KAPs) - Bamaga, Omar A. A.; Mahdy, Mohammed A. K.; Mahmud, Rohela; Lim, Yvonne A. L. (BioMed Central (BMC), Springer Nature, 2014)
Background: Yemen is a Mediterranean country where 65% of its population is at risk of malaria, with 43% at high risk. Yemen is still in the control phase without sustainable reduction in the proportion of malaria cases. A cross-sectional household survey was carried out in different districts in the southeast of the country to determine malaria prevalence and identify factors that impede progress of the elimination phase. Methods: Blood specimens were collected from 735 individuals aged 1-66 years. Plasmodium species were detected and identified by microscopic examination of Giemsa-stained thick and thin blood smears. A household-based questionnaire was used to collect demographic, socioeconomic and environmental data. Results: The overall prevalence of malaria was 18.8% with Plasmodium falciparum as the predominant species (99.3%), with a low rate of Plasmodium vivax detected (0.7%). The infection rate was higher in Al-Raydah and Qusyer districts (21.8%) compared to Hajer district (11.8%). Fifty-two percent of the persons positive for Plasmodium were asymptomatic with low parasite density. The adults had a higher infection rate as compared to children. Univariate analysis identified those whose household's head are fishermen (OR = 11.3, 95% CI: 3.13-40.5) and farmers (OR = 4.84, 95% CI: 1.73-13.6) as high-risk groups. A higher number of positive smears were observed in people living in houses with uncemented brick walls (OR = 2.1, 95% CI: 1.32-3.30), without access to toilets (OR = 1.6, 95% CI: 1.05-2.32), without a fridge (OR = 1. 6, 95% CI: 1.05-2.30), or without TV (OR = 1. 6, (95% CI: 1.05-2.30). People living in houses with water collection points located less than 200 meters away were also at higher risk of acquiring malaria (OR = 1.6, 95% CI: 1.05-2.30). Knowledge about the importance of using insecticide-treated mosquito nets (ITNs) and indoor residual spraying (IRS) for prevention of malaria was 7% and 2%, respectively. Conclusions: Several environmental, socioeconomic and behavioral issues were discovered to be the contributing factors to the high prevalence of malaria in southeast Yemen. Novel strategies adapted to the local situations need to be established in order to improve the effectiveness of malaria control.